Avaliação do sistema purinérgico na pitiose experimental em coelhos tratados com imunoterápico - Bach, Barbara Charlotte (2012)
Pythiosis is a disease caused by the oomycete Pythium insidiosum that affects horses, cattle, sheep, cats and humans, and occurs in tropical, subtropical and temperate regions. In horses the lesions are characterized by ulcerative eosinophilic granulomas. Most drugs are ineffective against this pathogen and immunotherapy has shown promise in the regression of the disease, even without the complete elucidation of the immune mechanisms involved. The purinergic system via adenine nucleotides (ATP and ADP) and its derivated nucleoside (adenosine), plays an important role in modulating the immune and inflammatory responses. Once released by cells, nucleotides interact with specific receptors and their extracellular concentrations are controlled by a group of ecto-enzymes, among which are ENTPDase (ecto-nucleoside triphosphate diphosphohydrolase) and ADA (adenosine deaminase). Taking into account the importance of immunotherapy in the treatment of pythiosis and a possible involvement of purinergic signaling in the immune response, the activities of E-NTPDase and E-ADA were evaluated in lymphocytes of rabbits with experimental pythiosis. For disease induction, zoospores were inoculated, subcutaneously, in the lateral region of the torax of each rabbit. These animals were evaluated weekly and the nodular area (cm2) developed was determined after 28 days of inoculation. Animals with experimental pythiosis, confirmed by enzyme immunoassay and the development of characteristic lesions, were treated with immunotherapy, whereas the ratio between the enzymatic activity in lymphopcytes and the consequent triggered immune response was investigated. Animals that did not develop lesions and those from the control group showed the same pattern of ectoenzymatic activity. E-NTPDase activity in lymphocytes of rabbits with experimental pythiosis was significantly higher (p<0,001) in relation to ATP hydrolysis (about 100%) and may be related to decreased (p<0,05) serum ATP (54,04%), when compared to the control group. After immunotherapeutic treatment, the activity of E-NTPDase showed similar values to those observed on the day of inoculation. Moreover, rabbits with experimental pythiosis showed a significant decrease (p<0,01) in the activity of E-ADA (82,36%), and this would lead to a significant increase in the extracellular concentration of adenosine (2,51 times), in relation to the control group (p<0,01). After immunotherapy, this group of animals showed a significant increase in the activity of E-ADA (78,62%) (p<0,01). Through this study, it can be observed that an increased activity of E-ADA, during pythiosis, leads to extracellular regulation of ATP and adenosine concentration. As a result, low levels of extracellular ATP could activate P2Y receptors, while high levels of extracellular adenosine may activate A2A and/or A2B receptors, triggering a TH2 response, responsible for the tissue damage generated by infection. After immunotherapy, it can be observed an inversion in the behaviour of the enzymatic activities, stimulating a TH1 response in the host. The switch from a TH2 response, responsible for the injuries that occur on pythiosis, to a TH1 response, is the most accepted hypothesis to explain the healing properties of immunotherapy. Thus, it is suggested the involvement of purinergic system in the pattern of immune response that occurs during pythiosis and after immunotherapy.